Effective regulation of upconversion luminescence in NaErF4 and NaErF4@SiO2 core-shell particles. Issue 10 (15th May 2022) - Chen, Jie; Gao, Yixin; Wang, Chao; Yin, Yu; Song, Jiaxing; Zeng, Xiaodan; Liu, Zhigang; Jiang, Haifeng
Abstract: Upconversion luminescence materials have gained extensive attentions owing to their unique luminescence characteristics of converting near-infrared excitation to visible light emission. However, how to improve the doping concentration of activator (usually <3 mol%) in traditional sensitizer-activator system is still a great challenge due to the luminescence quenching effect. In this work, NaErF4 crystals with diverse crystal phases and morphologies were prepared by simple hydrothermal method, constructing a 100% doping concentration system of activator (Er 3+ ). With the increase of F − content, the phase of NaErF4 transfers from cubic to hexagonal, and the morphology changes from nanospheres to hexagonal microflakes, meanwhile, the upconversion luminescence intensity also increases gradually. In addition, in order to further inhibit the luminescence quenching effect of NaErF4 bare core, a series of NaErF4 @SiO2 core-shell samples with different SiO2 shell thickness were successfully prepared. Compared with NaErF4 bare core, the morphology and structure of the NaErF4 @SiO2 core-shell samples have no obvious change, but the UC luminescence intensity is significantly enhanced. Interestingly, the change of NaErF4 crystal phase and SiO2 shell thickness can both bring about multicolor luminescence. In addition, different from the traditional NaYF4 :Yb, Er co-doping system, the as-prepared hydrophilic NaErF4 and NaErF4 @SiO2 samples showed a greater red to green ratio (R/G > 1), which may expand their potential applications in biological imaging and sensing fields.